INTERNATIONAL APPROACHES TO DEFINING OPERATIONAL RISK AND INTRODUCTION IN UKRAINE - Дмитренко, Ірина (Socio-economic relations in the digital society, 2019)
Globalization processes in the economic sphere cause the need to make the updating of legislative and regulatory Ukrainian acts on banking supervision according to the common international regulatory standards. The big challenge of such updating is sizing capital for operational risk. Basel Committee on Banking Supervision introduced a new approach for calculating operational risk capital which is named the standardized approach. The article considers and analyzes a new approach of assessing the operational risk and operational risk capital requirements, proposed by the Basel Committee on Banking Supervision. The new standardized approach for measuring minimum operational risk capital requirements replaces all existing approaches. A new approach is based on a single indicator of operational risk exposure, such as Business Indicator. Based on the qualitative and quantitative analysis, the Basel Committee on Banking Supervision has identifi ed the Business Indicator as the most suitable replacement for Gross Income, as it addresses most of the latter’s weaknesses. The main elements of calculating of the new standardized approach are considered and analyzed in the article. At the same time article includes propositions about implementation of the prudential requirements for calculating operational risk capital in Ukrainian legislative sphere, while suggesting the opportunity of the implementation step by step the new standardized approach for the calculating operational risk capital with taking into consideration the features of the regulatory framework of Ukraine. Also suggested methods of improving the assessment of the capital adequacy of Ukrainian banks in accordance with international standards accepted in many countries and based on risk-oriented methodology for calculating the adequacy of bank capital.
Keywords: operational risk; capital; assessment; approach; Basel Committee on Banking Supervision; capital adequacy; standardized approach; Business Indicator